A qualitative exploration of fatherhood after acquired brain injury (ABI). Issue 9 (21st October 2022) - Cregan, Karen; Daisley, Audrey; Ford, Catherine; Gracey, Fergus
ABSTRACT: Acquired Brain Injury (ABI) significantly affects individuals across multiple areas of intimate, familial, and parental domains. Gender and identity are pivotal research areas in navigating life after ABI. To date, scant research has explored gendered experiences, particularly those related to the masculine lifeworld. This study aimed to explore how men who were fathers before their injuries experience fatherhood after ABI. An Interpretative phenomenological analysis (IPA) methodology was used, and seven fathers participated in the semi-structured interviews (time since injury 1-18 years, age range 27-66 years) which explored their meaning-making. Four superordinate themes were drawn from all interviews through engaging with the qualitative research process: (1) what being a father means, (2) altered relationships with others, (3) becoming lost and finding their way through, and (4) renewed fatherhood. The findings show intersectionality between pre-and post-injury comparisons of self and social identities, alongside the contextual and societal identities in the subjective fathering experiences. Through increased understanding, we may enable fathers to find new ways to resolve, reformulate, and connect to move into their future possible fatherhood. The importance of this research is in giving voice to these less represented men so that we may shape our understanding to aid future fathers post-ABI.